2002
DOI: 10.1002/jbm.10331
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte response to retrieved polymethylmethacrylate particles

Abstract: The purpose of this study was to compare retrieved polymethylmethacrylate (PMMA) particles from failed total hip arthroplasties in terms of size, shape, and the response of human monocytes with commercially available particles. PMMA particles were isolated from peri-implant tissues of five failed cemented total hip arthroplasties using tissue digestion and a sucrose density gradient technique. Prepolymerized cement powder and those from which barium sulfate had been removed were examined for comparison. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Moreover, these results suggested that activated macrophages did not produce soluble mediators capable to activate other macrophages at distance. Miyaguchi et al have found that macrophages, in response to poly (methylmethacrylate) debris, were activated and released cytokines such as IL-6 and TNF-a [15]. These soluble factors are known to activate other cell types participating in the inflammatory response and also promote osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, these results suggested that activated macrophages did not produce soluble mediators capable to activate other macrophages at distance. Miyaguchi et al have found that macrophages, in response to poly (methylmethacrylate) debris, were activated and released cytokines such as IL-6 and TNF-a [15]. These soluble factors are known to activate other cell types participating in the inflammatory response and also promote osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Macrophages mediate inflammation by the secretion of inflammatory mediators, such as coagulation factors, lysosomal enzymes (tartrate resistant acid phosphatase-TRAcP, alpha naphthyl acetate esterase-ANAE, etc. ), cytokines (IL-6, TNF-a), reactive oxygen species (ROS) and growth factors [15,16]. Macrophages are responsible of the elimination of foreign bodies in the organism; they can fuse to form multinucleated giant cells, and monotype/macrophages derive from the same haematopoietic stem all (CFU-GM) (see reviews in [17,18]).…”
Section: Introductionmentioning
confidence: 99%
“…It is found however that bone cement debris causes less stimulation of the immune system than do artificially generated PMMA particles [Miyaguchi et al, 2002]. PMMA particles are found to generate an immune response in mice but the nature of the response is not the same as other polymers [Tomazic-Jezic et al, 2001].…”
Section: Debris Release and Inflammation Of Surrounding Tissuesmentioning
confidence: 94%
“…O trabalho confirmou o resultado anterior 21 de que o procedimento cirúrgico ortopédico (particularmente endoprótese) usando cimento ósseo foi um fator de risco independente para tremor. Uma explicação possível para isso seria a liberação de citocinas (como fator de necrose tissular-alfa e interleucina-6) estimulada pelo cimento ósseo polimetilmetacrilato 40 . A intervenção cirúrgica de longa duração foi associada à maior freqüência de tremor.…”
Section: Fisiopatologiaunclassified
“…The study confirmed a previous work 21 that showed that orthopedic surgeries (especially endoprosthesis) using bone cement was an independent risk factor for the development of tremors. A possible explanation would be the release of cytokines (tumor necrosis factor-alpha and interleukin-6) stimulated by the bone cement polymethylmethacrylate 40 . Prolonged surgeries were associated with a higher incidence of tremors.…”
Section: Physiopathologymentioning
confidence: 99%